The use of skeletal parameters as predictors of growth in the timing and modality of orthodontic treatment among seven to seventeen year old Filipino students - Reyes, Martin Antonio V.
In the field of orthodontics, the diagnosis and treatment planning of a patient in the adolescent stage requires an evaluation of the individual's growth rate. It is through the assessment of growth and development that the orthodontist can find out the reasons for the existence of a malocclusion and decide when is the most appropriate time to begin any form of treatment. Because of the variable growth patterns known to exist among individuals, chronological age is not a good indicator of growth status. Growth is best studies on the basis of skeletal maturation, which is the degree of ossification of bone. #The hand-wrist radiograph finds its usefulness in the assessment of skeletal maturation. The ossification of the carpal and sesamoid bones, the metacarpals of the hand, and the phalanges of the fingers form a chronology of skeletal deveopment. It is thus the gold standard for skeletal maturation assessment. #Recent studies however have shown that the development of cervical vertebrae as seen on the lateral cephalogram have also shown a chronology of events leading to skeletal maturation. A positive correlation between both methods of skeletal assessment could imply an alternative use of the lateral cephalogram in the assessment of the growth and development of the individual.
Vita.
Thesis (Master of Science in Dentistry) -- University of the Philippines Manila
Keywords: Skeleton -- Growth; Orthodontics